Spectral Investigation of Complex Ions Formation with Dye Indicators in Different Metal Systems - N. Modi, Ashwin; Desai, C.M. (Asian Journal of Chemistry, 2010)
The absorbance of zinc chloride-alkali halide, zinc chloride-alkali halidewith potassium perchlorate and copper chloride /nickel chloride-zincchloride systems were studied by dye indicators and shows peaks correspondingto complex ion formation between salts.